DROP SPECTRUM IN BACKPACK SPRAYERS IN SCARLET EGGPLANT CULTURE (Solanum aethiopicum) (Colloquium Agrariae. ISSN: 1809-8215, 2022)
The use of manual back sprayers is common on rural properties for the application of phytosanitary products with different types of tips. The aim of the study was to evaluate the droplet spectrum in spray syrups on the jilo tree crop. The study was in a randomized block design (DBC) with a 2x3 factorial scheme, consisting of two working pressures 103.421 kPa and 310.264 kPa and three spray tips with four blocks. For the acquisition of information, hydrosensitive papers were used, which later had their images digitized and analyzed using the Gotas® software. Values ​​were extracted from: number of drops, dispersion, applied volume, coverage and DMV. Then, the values ​​found were submitted to the “F” test at 5% probability and, according to significance, were compared by Tukey's test at 5% probability. For each factor, the coefficients of variation were evaluated separately and then an analysis of the correlation between these factors. The highest pressure produced the greatest number of drops and application coverage. Coverage was also the best in this pressure with the highest percentage of coverage.